PARTISIPASI MASYARAKAT DALAM MENERAPKAN SISTEM AGROFORESTRY PORANG (AMORPHOPALLUS MUELLERI BLUME) DALAM MENJAGA KELESTARIAN HUTAN WILAYAH KERJA KPH SARADAN (STUDI KASUS: DI DESA KLANGON KECAMATAN SARADAN KABUPATEN MADIUN PROVINSI JAWA TIMUR) - Puput Fitriana; Wilhelmina Seran; Mamie E Pelondo'u (Wana Lestari, 2021)
This study aims to 1). Knowing the level of community participation in the agroforestry system of porang (Amorphopallus muelleri Blume); 2). Knowing agroforestry system that is applied to perverse forests the working area of KPH Saradan. This research was conducted in Agroforestry forest of porang the working area of RPH Klangon, BKPH Pajaran, KPH Saradan, District Madiun, Region of Est Java. The survey method was conducted in December 2018- February 2019. Data collected in the form of primary data and secondary data. Primary data was interview method and secondary data obtained from the documents, archive, report, and stakeholders. This study analyz to Skala likert method.The results of research showed that 1). Based on the percent (%) index calculation, community participation a results value of 67,68% which is included in the high category. 2). Agroforestry system applied in Klangon village is agrosilvicultural system that combines (intercropping) between annual plant (Jati, Mahoni, and Sonokeling) with annual crops (Porang).